2020
DOI: 10.3847/1538-4357/abca88
|View full text |Cite
|
Sign up to set email alerts
|

Supernova Explosions in Accretion Disks in Active Galactic Nuclei: Three-dimensional Models

Abstract: Supernova (SN) explosions can potentially affect the structure and evolution of circumnuclear disks in active galactic nuclei (AGN). Some previous studies have suggested that a relatively low rate of SN explosions can provide an effective value of alpha viscosity between 0.1 and 1 in AGN accretion disks within a 1 pc scale. In order to test this possibility, we provide some analytic scalings of the evolution of an SN remnant embedded in a differentially rotating smooth disk. We calibrate our estimates using th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
13
1
Order By: Relevance
“…Regardless, these massive stars are expected to leave behind neutron stars and stellar-mass black holes within the disk, and can potentially produce electromagnetic signatures. Supernovae may transport significant angular momentum through the disk (Moranchel-Basurto et al 2021), and are a possible source of transients observed in optical time-domain surveys (Frederick et al 2020;Graham et al 2017). Many AGN stars are expected to reach the end of their lives rapidly rotating due to the angular momentum gained as they accrete, so black holes formed in the collapse of AGN stars could generate gamma-ray bursts, which could in turn take on a number of appearances depending on their location in the accretion disk (Jermyn et al in prep.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…Regardless, these massive stars are expected to leave behind neutron stars and stellar-mass black holes within the disk, and can potentially produce electromagnetic signatures. Supernovae may transport significant angular momentum through the disk (Moranchel-Basurto et al 2021), and are a possible source of transients observed in optical time-domain surveys (Frederick et al 2020;Graham et al 2017). Many AGN stars are expected to reach the end of their lives rapidly rotating due to the angular momentum gained as they accrete, so black holes formed in the collapse of AGN stars could generate gamma-ray bursts, which could in turn take on a number of appearances depending on their location in the accretion disk (Jermyn et al in prep.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…The 2D simulations we present do not take into account the shearing motions of the disc. In reality, the hole excavated by the SN will be elongated in the disc rotation direction (Moranchel-Basurto et al 2021).…”
Section: Disc Feedbackmentioning
confidence: 99%
“…SNe in AGNs were studied in the context of the feedback on the AGN structure and evolution (Rozyczka et al 1995;Ferrara & Tolstoy 2000;Moranchel-Basurto et al 2021). Here we focus on the observational signatures of SN explosions in AGN discs.…”
Section: Introductionmentioning
confidence: 99%
“…The outer parts of the accretion disk of supermassive black holes (SMBHs) in active galactic nuclei (AGNs) host many poorly understood, complicated processes. Star formation is unavoidable in these regions because of self-gravity (Paczyński 1977;Kolykhalov & Sunyaev 1980;Shlosman & Begelman 1989;Collin & Zahn 1999;Goodman 2003;Goodman & Tan 2004;Collin & Zahn 2008), producing compact stellar remnants from the rapid evolution of massive stars (Artymowicz et al 1993;Cheng & Wang 1999;Cantiello et al 2021;Moranchel-Basurto et al 2021;Wang et al 2021;Grishin et al 2021). Stellar evolution rapidly releases metals into the outer parts of the self-gravitating (SG) disk (Wang et al 2010(Wang et al , 2011(Wang et al , 2012, offering an explanation for the super-solar metallicities observed in AGNs across cosmic time (Hamann & Ferland 1999;Warner et al 2003;Nagao et al 2006;Shin et al 2013;Du & Wang 2014).…”
Section: Introductionmentioning
confidence: 99%